2007
DOI: 10.1073/pnas.0609063103
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between singlet oxygen- and hydrogen peroxide-dependent signaling of stress responses in Arabidopsis thaliana

Abstract: ascorbate peroxidase ͉ chloroplast ͉ oxidative stress ͉ reactive oxygen species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
241
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(250 citation statements)
references
References 43 publications
8
241
0
1
Order By: Relevance
“…The role of 1 O 2 is still not well known as compared with other ROS, but recent findings suggest a function in signaling and its involvement in the response to pathogens (Vellosillo et al, 2010). A cross talk between 1 O 2 -and H 2 O 2 -dependent signaling has been reported to occur during certain environmental stress conditions (Laloi et al, 2007). It is thus possible that 1 O 2 is a major signaling factor of root border-like cells under biotic stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of 1 O 2 is still not well known as compared with other ROS, but recent findings suggest a function in signaling and its involvement in the response to pathogens (Vellosillo et al, 2010). A cross talk between 1 O 2 -and H 2 O 2 -dependent signaling has been reported to occur during certain environmental stress conditions (Laloi et al, 2007). It is thus possible that 1 O 2 is a major signaling factor of root border-like cells under biotic stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3C). Additional evidence of a close correlation between 1 O 2 accumulation and cell death in ch1 was obtained by monitoring H 2 O 2 and 1 O 2 -specific marker genes (Gadjev et al, 2006;Laloi et al, 2007). We analyzed the relative expression levels of two H 2 O 2 -responsive genes and two 1 O 2 -responsive genes (Fig.…”
Section: O 2 Generation Induces Cell Death In Arabidopsis Leaf Tissuesmentioning
confidence: 99%
“…All PCR reactions were performed in triplicate on material from two biological repeat experiments. The H 2 O 2 -specific genes used were At1g49150 (unknown protein) and At1g62380 (ACO2), the 1 O 2 -specific genes At5g10830 (embryo abundant protein-like) and At3g61190 (BAP1; Gadjev et al, 2006;Laloi et al, 2007). Universal ProbeLibrary probes (Roche Applied Science) and primers used can be found in Supplemental Table S2.…”
Section: Rna Isolation and Quantitative Reverse Transcription-pcrmentioning
confidence: 99%
“…In wild-type plants treated with 3-(3,4-dichlorophenyl)-1,1-dimethylurea, an inhibitor of oxidation of the primary quinone electron acceptor of PSII and, consequently, photosynthetic electron transport, the production of 1 O 2 in PSII reaction centers is increased, and in these circumstances, the EXE1/EXE2 pathway promotes cell death (Wagner et al, 2004). The presence of an antagonistic anti-cell death system, involving signaling by the ROS hydrogen peroxide (H 2 O 2 ), has been demonstrated that counteracts the EXE1/EXE2 pro-cell death pathway (Laloi et al, 2007). The H 2 O 2 anti-cell death pathway may control the capacity of the cell to quench 1 O 2 signaling by regulating lipid-soluble antioxidant levels and control of the repair of photodamaged D1 protein, a component of the PSII reaction center.…”
Section: O 2 Signalingmentioning
confidence: 99%